Copper nanoparticles (CuNPs) increase the vase life of cut carnation and chrysanthemum flowers: antimicrobial ability and morphophysiological improvements - Rashidiani, Nahid; Nazari, Farzad; Javadi, Taimoor; Samadi, Saadi (Ornamental Horticulture, 2020)
This research was carried out to evaluate the effects of copper nanoparticles (CuNPs) on the postharvest physiology of carnation and chrysanthemum cut flowers. Synthesized CuNPs were applied at 10 and 20 mg L-1 to both cut flowers by the pulsing method. The physicochemical characteristics and the activity of antioxidant enzymes were measured on 0, 3, 6 and 9 days along the vase life. According to heat map analysis, changes in measured parameters were affected by flower type > vase period > CuNPs concentration. Results also showed that treating the two species of cut flower with CuNPS by the pulse treatment improved the relative fresh weight (RFW), vase solution uptake (VSU), membrane stability index (MSI), flower diameter and total soluble carbohydrate (TSC). Meanwhile, a decrease in both bacterial population of the stem end and the hydrogen peroxide (H2 O2 ) was observed. In comparison with the control, CuNPs at 20 mg L-1 by pulse treatment almost increased the vase life in both cut flowers by 30%.